Coping Stress: How Students Cope with Academic Stress? - rachmawati, Ulvina; Widiatmoko, Mualwi; Malasari Ardini, Fadhila; Putra Ayu Distira, Riski; Ayu Salsabila, Nimas (Journal of Education and Counseling (JECO), 2023)
Academic stress is a psychological condition where students feel worried about academic failure. To overcome this, students can develop stress coping, be it problem focused coping or emotional stress coping. This study was conducted to provide an overview of the level of stress coping developed by students as well as the types of stress coping developed. This study is a quantitative descriptive study with a population of Nahdlatul Ulama Sunan Giri University students. The sample used in this research was 300 students. The instrument used in this study is a stress coping scale using the stress coping theory developed by Lazarus. The results show that students have moderate stress coping abilities. The type of stress coping that is most often used by both male and female students in dealing with academic stress is emotional focused coping. The forms of behavior used to overcome academic stress are distancing, confrontative coping, and seeking information support.